(untitled) (Latakia University Journal -Engineering Sciences Series, 2018)
يهدف البحث إلى تقييم الجودة في مشاريع التشييد في سوريا من وجهة نظر الزبائن ومن مراقبة واقع تنفيذ المشاريع وتحديد نسبتها مقارنة بالأساليب والمقاييس العالمية المعتمدة لذلك ومن ثم تحديد الأسباب والعوامل المؤثرة على جودة تنفيذ المشاريع. لتحقيق ذلك قمنا في البحث بتقييم الجودة وتحديد المشاكل المتعلقة بها في عينة من مشاريع التشييد المنفذة في العام 2015 وذلك بقياس رضا الزبون الخارجي و الداخلي حيث كانت نسبة رضا الزبون الاجمالية 59.63% وهي تحتاج لتحسين ، وتم أيضا قياس نسبة المطابقة لمتطلبات الجودة باستخدام قوائم التحقق وفق معايير برنامج إدارة الجودة BIM 360 field وكانت نسبة المطابقة 88.79 % وهي تشير إلى وجود مشكلة حقيقة وفق المعايير العالمية لذلك. ثم تم تحديد المشكلات والانحرافات المتعلقة بالجودة و تحديد وتحليل الأسباب المؤدية لحدوث هذه المشكلات والتي صنفت إلى ثلاثة عوامل وهي القوانين والأنظمة والالتزام بها وعوامل فنية وعوامل إدارية وهي تشكل الأساس الذي يجب ان يتم الاستناد إليه لوضع أي إطار عمل أو أي محاولة لتحسين جودة المشاريع ،وخلص البحث إلى ضرورة العمل من قبل الجهات المعنية على إعادة صياغة القوانين المتعلقة بالأعمال الهندسية وتطويرها مع تحديد النظم والإجراءات لتحسين العوامل الفنية والإدارية في المشاريع. The research aims to assess the quality of Syrian construction projects from costumers’ point of view and by field observations during projects execution, also identifying quality level compared to international standards and identify the causes and factors of its defects. In order to achieve the research goal the quality was assessed and defects were identified for a sample for executed projects using customer satisfaction questionnaires and quality checklists .The result of customer satisfaction was 59.63% which indicates that it needs improvement and the result of quality checklists of BIM 360 field software was 88.79% which indicate that it is a real problem compared to international standards. Then defects and their causes were identified and analyzed and the factors of quality defects were classified in three main scopes which are the regulations and its implementation, managerial factors, and technical factors which form the base for any future framework or effort for quality improvement, and the research concluded the importance of reformulate the construction regulations by relevant parties and taking into consideration the managerial and technical procedures development.